2022
DOI: 10.33222/pelitapaud.v6i2.1974
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Dongeng Digital dalam Meningkatkan Keterampilan Menyimak Anak Usia 5 – 6 tahun

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh dongeng digital dalam meningkatkan keterampilan menyimak anak usia 5 – 6 Tahun. Penelitian ini adalah penelitian kuantitatif dengan metode penelitian eksperimen yang menggunakan teknik pengumpulan data berupa observasi dan dokumentasi. Hasil penelitian dongeng digital terhadap keterampilan anak usia 5 – 6 tahun berpengaruh positif. Hal ini dapat dibuktikan dari hasil nilai Sig. Uji One Way Anova bernilai 0.000 < 0.005 yang berarti adanya perubahan signifika… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…Thus, it can be said that digital fairy tales can have a significant influence on the vocabulary skills of Javanese Krama (Bahasa Jawa Krama) children at TK Dharma Wanita Ngimbang Lamongan. Fuadah, Tiara, and Pratiwi (2022) aimed to determine the effect of digital fairy tales in improving the listening skills of children aged 5-6 years. This research is quantitative research with experimental research methods that use data collection techniques in the form of observation and documentation.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it can be said that digital fairy tales can have a significant influence on the vocabulary skills of Javanese Krama (Bahasa Jawa Krama) children at TK Dharma Wanita Ngimbang Lamongan. Fuadah, Tiara, and Pratiwi (2022) aimed to determine the effect of digital fairy tales in improving the listening skills of children aged 5-6 years. This research is quantitative research with experimental research methods that use data collection techniques in the form of observation and documentation.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…It even complements the results of previous research. One of them is the research of Fuadah, Tiara, and Pratiwi (2022) and Luthfiah and Wijayanto (2021) which found that the use of digital fairy tales has proven to be influential in improving children's learning outcomes related to aspects of children's language development, namely listening skills using digital fairy tale media rather than conventional fairy tales.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kajian terdahulu pernah dilakukan oleh (Fuadah et al, 2022) Penelitian tersebut mengkaji pengaruh digital apakah dapat mingkatkan salah satu keterampilan yaitu menyimak atau tidak yang diujikan pada anak usia 5-6 tahun. Penelitian tersebut menggunakan eksperimen sebagai metodenya serta pendekatan kuantitatif .Hasil penelitian menunjukkan adanya pengaruh positif dari dongen digital pada kemampuan menyimak anak usia 5-6 tahun.…”
Section: Pendahuluanunclassified